Storing solar energy in continuously moving redox particles – Experimental analysis of charging and discharging reactors. (15th February 2022) - Tescari, Stefania; Neumann, Nicole Carina; Sundarraj, Pradeepkumar; Moumin, Gkiokchan; Rincon Duarte, Juan Pablo; Linder, Marc; Roeb, Martin
Highlights: Experimental demonstration of a rotary kiln for reduction, and a moving bed reactor for oxidation. Solar rotary kiln for charging storage at rate of 10 kg/h, and incident power of 10 kW. Moving bed for heat release at particles rate of 10–15 kg/h, and gas 50–150 l/min. Rotary kiln could heat particles to over 1000 °C and react to conversion up to 70% Moving bed could heat gas flow to around 880 °C and oxidize 67% − 100% of reduced particles. Feasibility of a conceptual reactor coupling is discussed. Abstract: The ability to store energy in the form of high-temperature heat is one of the key advantages of concentrated solar energy over other renewable sources. Higher energy densities compared to the state of the art can be achieved through a wider range of operating temperatures and by adding chemical energy storage. Thermochemical storage (TCS) systems can operate in almost any temperature range, depending on the material chosen, providing high energy densities through a reversible reaction and allow long-term storage. This work shows the development and experimental evaluation of a complete pilot-scale TCS system. The storage material is a metal oxide, namely manganese-iron oxide, which undergoes consecutive reduction (endothermic) and oxidation (exothermic) reaction cycles. The metal oxide is shaped into mm-size granules. The TCS cascade applies two reactors: one operating on-sun and used to store the solar energy and a separate one, operating off-sun, for the release of heat. The first reactor is a solar rotary kiln that transfers concentrated solar energy directly to the reactive particles, which are heated and reduced. The heat is released afterwards from the particles to the air flowing countercurrent, in a vertical moving bed reactor. Here, both sensible and chemical energy generated by the reverse chemical oxidation reaction is transferred. The continuously operated rotary kiln can heat up about 10 kg/h of particles to an outlet temperature of close to 1000 °C and achieve a maximum conversion of about 70 %. The moving bed, which can be operated continuously 24 h, has a similar particle mass flow and can heat 150 l/min from 300 C to 880 °C. The reactors allowed the storage and release of up to 2.1 kW of thermal power.